HUBUNGAN PENGETAHUAN REMAJA PUTRI TENTANG KEPUTIHAN DENGAN PRILAKU PENCEGAHAN KEPUTIHAN DI SMA NEGERI 2 VII KOTO SEI. SARIK KABUPATEN PADANG PARIAMAN - Prasetyaningsih, Prasetyaningsih (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2023)
Leucorrhoea is a symptom in the form of a liquid that is not in the form of blood coming out of genetalorgans. In Indonesia, about 90% of women have the potential to experience leucorrhoea because thecountry of Indonesia is a tropical climate, so young fungi develop which result in many cases ofleucorrhoea. Leucorrhoea in teenagers can be caused by bad behavior of leucorrhoea precaution.Knowledge is a factor to build behavior in teenager. This study aims to analyze the correlation betweenlevel knowledge about leucorrhoea with prevention behavior leucorrhoea for teenage girls at SMANegeri 2 VII Koto Sei. Sarik Kabupaten Padang Pariaman in February 2020. The type of research isquantitative by using descriptive correlation design method with cross sectional approach. Population ofall Teenage Girls class XI and XII at Sei. Sarik as many 50 people. The technique sampling is usingsimple random sampling with total sample of 50 respondents. Data processing was univariate andbivariate with Chi-Square test. The results showed that more teenager with good knowledge ofleucorrhoea have good behavior in leucorrhoea precaution (70%). The results of the statistical tests showthat there is a significant correlation with the strong strength between knowledge about Leucorrhoea withprevention behavior leucorrhoea for teenage girls at SMA Negeri 2 VII Koto Sei. Sarik, with acorrelation coefficient of 0027. The higher adolescent's knowledge, it will better for behavior ofadolescents towards prevention of leucorrhoea. Based on this study, it is recommended that healthworkers be expected to work together with schools in providing information to students aboutreproductive health, especially leucorrhoea.